(3YdGbI EOeGf GdWYGe HCMOGK GdMjGI GdVGZWI h feW GdMjGI dOi YjfI ef GdeQGgbGJ (B: s (3OQGSI GQJHGWjI ebGQfI (B/ s - (3QfG MSjf eMeO GdMGaXs; (3CMeO NjQi MGaX (B: s; (3QTG YHOGdaJGM GdOjOi (B: s ((3GdbGgQI (B: s (3QfG MSjf eMeO GdMGaX (B: s, 2021)
(3JgOa gPg GdOQGSI Edi(B: (3GdJYQa Ydi GdYdGbI Hjf EOeGf GdWYGe h CMOGK GdMjGI GdVGZWI dOi GdeQGgbGJ(B: (3h GdJYQa Ydi GdYdGbI Hjf EOeGf GdWYGe h feW GdMjGI (B((3GdUMi(B) (3dOi GdeQGgbGJ(B. (3GdJYQa Ydi GdaQhb Hjf GdeQGgbGJ GdeOefGJ Ydi GdWYGe h GdeQGgbGJ ZjQ GdeOefGJ Ydi GdWYGe(B: (3ai CMOGK GdMjGI GdVGZWI h feW GdMjGI(B. (3GdefgL(B: (3GSJNOeJ GdHGMKI GdefgL GdhUai GdebGQf(B: (3h JchfJ GdYjfI ef (B(200) (3eQGgbI(B: (3GfbSeJ Gdi (B(100) (3eQGgbI eOefI WYGe (B- (3eeG jJQOOf Ydi YjGOGJ GdSefI h GdJZPjI(B: (3h (B(100) (3eQGgbI ZjQ eOefI Ydi GdWYGe ef WGdHGJ GdeOGQS (B. (3h QGYJ GdHGMKI GdNUGFU GdOjeLQGajI GdCNQi(B. (3GdCOhGJ(B: (3JchfJ ef ebjGS EOeGf GdWYGe (B((3EYOGO(B: (3LjQgGQJ(B: (3chQjf(B: (3HQhfd (B- 2009: (3JQLeI(B: (3QMGH eMeO fLjH (B- 2014). (3ebjGS feW GdMjGI (B((3EYOGO(B: (3ei(B-(3jf JTjf h RedGFg (B- 2003: (3JQLeI GdHGMKI(B). (3ebjGS ehGba GdMjGI GdVGZWI (B((3EYOGO(B: (3RjfH eMehO TbjQ (B- 2003). (3GdfJGFL(B: (3JhLO YdGbI GQJHGWjI ehLHI OGdI YfO eSJhi (B(0.01) (3Hjf eLehY EOeGf GdWYGe(B: (3h VZhW GdMjGI(B. (3h JhLO YdGbI GQJHGWjI SGdHI OGdI YfO eSJhi (B(0.01) (3Hjf eLehY EOeGf GdWYGe h cd GHYGO feW GdMjGI(B. (3ceG JhLO aQhb OGdI OGdI YfO eSJhi OdGdI (B(0.01) (3ai VZhW GdMjGI Hjf GdeOefGJ Ydi GdWYGe h ZjQ GdeOefGJ dUGdM GdeOefGJ(B: (3h JhLO aQhb OGdI OGdI YfO eSJhi OdGdI (B(0.01) (3ai GfeGW GdMjGI Hjf GdeOefGJ Ydi GdWYGe h ZjQ GdeOefGJ dUGdM ZjQ GdeOefGJs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI Yjf TeS (B- (3cdjI GdCOGH (B- (3bSe Yde GdfaSs
Keywords: (3CMOGK GdMjGI GdVGZWIs; (3EOeGf GdWYGes; (3feW GdMjGIs